Innovation and Commercialization of Indonesian Traditional Food in the Industrial Era 4.0 - Ardiansari, Anindya; Ahmadi, Farid; Ridloah, Siti; Ridloah, Siti; Widia, Syam (International Journal of Research Innovation and Entrepreneurship, 2020)
The industrial revolution 4.0 considers an information technology-based human life. In this practical modern era, the choice of food types has been very diverse. Consuming modern food (fast food) has been a common choice for urban community with busy activities. In addition, restaurants that sell (Indonesian) traditional food were hard to find. Time consuming or less practical to prepare the food was the most possible reason of the decrease in the consumption of this kind of food. This phenomenon encourages efforts to improve people’s attention towards this traditional food to conserve its existence by diversification of the traditional food. It is important to introduce and incorporate Indonesian traditional food in industries, in response to the challenges of the industry's revolutionary era. This research is an exploratory study with a mixed method approach. The population in this study was small and medium size enterprises (SMSE) in Semarang city, Indonesia. Fifty SMSEs were involved in this study, with various traditional food products for sale such as Batagor, Pecel, Kupat Tahu with vegetables, Rujak, Lunpia, Rendang, Gudeg, Getuk, etc. A 12% of micro small and medium size enterprises (MSMSE) of traditional foods improved the quality of the produced food through a product innovation, whereas a 20% of SMSEs through a process innovation. Furthermore, marketing and organizational innovation were done by 78% and 4% SMSE, respectively. The traditional food producers showed a low level of innovation readiness, indicating their incapability in the implementation of innovation. Supports from many parties were needed to maintain the existence of the traditional food in their competition with the modern ones.